Diagnosis of Vertical Root Fractures by Cone-beam Computed Tomography in Root-filled Teeth with Confirmation by Direct Visualization: A Systematic Review and Meta-Analysis - PradeepKumar, Angambakkam Rajasekharan; Shemesh, Hagay; Nivedhitha, Malli Sureshbabu; Hashir, M Mohamed Jubair; Arockiam, Selva; Uma Maheswari, Tirupambaram Natarajasundaram; Natanasabapathy, Velmurugan (Journal of endodontics, 2021)
The purpose of this review was to determine the diagnostic accuracy of cone-beam computed tomographic (CBCT) imaging in detecting vertical root fractures (VRFs) in root-filled teeth compared with a reference standard (direct visualization). Electronic searches were performed in Medline, Scopus, Cochrane, and gray literature for English language articles until June 2020. Prospective and retrospective clinical studies using CBCT imaging to diagnose VRFs in root-filled teeth were included. Case reports and in vitro studies were excluded. The Quality Assessment of Diagnostic Accuracy Studies 2 tool was used to assess the risk of bias and applicability concerns. Meta-analysis was performed using Stata 16.1 software (StataCorp, College Station, TX) via the MIDAS v.3.0 package and METANDI module. Publication bias was evaluated using Deeks' funnel plot analysis. Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) was performed to evaluate the certainty of evidence. This systematic review was registered in the Open Science Framework (10.17605/OSF.IO/7JKE2). Eight articles were included in this systematic review and meta-analysis. Risk of bias assessment showed that 5 articles in the patient selection domain had low risk of bias with low applicability concern. In the index test and reference standard domains, 7 articles had moderate risk of bias with moderate applicability concern. Three articles had high RB in the flow and timing domain. There was no publication bias. CBCT imaging had a pooled sensitivity and specificity of 0.78 (95% confidence interval [CI], 0.64-0.88) and 0.80 (95% CI, 0.63-0.91), respectively, and an accuracy of 0.86 (95% CI, 0.83-0.89). CBCT imaging also had pooled positive and negative likelihood ratios of 4 and 0.2, respectively. In GRADE analysis, the quality of evidence was low for sensitivity and moderate for specificity when CBCT imaging was used for the diagnosis of VRF. The overall quality assessment of the included articles showed that in the patient selection domain, the risk of bias was low, and it was moderate in the index test and reference standard domains. Evidence from this systematic review and meta-analysis indicates that CBCT imaging is still not a good tool for diagnosing VRFs in root-filled teeth compared with direct visualization.